Perbedaan Pengaruh Terapi Relaksasi Dzikir Dan Hipnosis Lima Jari Terhadap Kecemasan Pada Ibu Hamil Primigravida di Puskesmas Tempel II - Zusinta Asri Dasri; Melania Wahyuningsih; Eko Mindarsih (HEALTH CARE : JURNAL KESEHATAN, 2021)
Pregnancy is a time that can cause stress or anxiety that can lead to mental disorders. Excessive anxiety that is felt in pregnant women can have a negative impact on the fetus and himself. This study aims to determine the difference in the effect of dzikir relaxation therapy and five finger hypnosis to reduce anxiety in primigravida pregnant women.The research method used was pre and post test without control group by giving therapy of dzikir relaxation and five-finger hypnosis. The sample technique used consecutive of 40 primigravida pregnant women as the subject. The analysis used the Wilcoxon test. And Mann Withney T-Test. The bivariate analysis of the pre test and post test values ​​in Dzikir and Five Finger Hypnosis showed p value = 0.000 (p <0.05). Meanwhile, the results of the bivariate analysis of the post test scores in Dzikir and Five Finger Hypnosis showed p value = 0.246 (p> 0.05). There is no significant difference between the two treatment groups. Keywords: Anxiety, Pregnancy, Dzikir Relaxation, Five Finger Hypnosis.